Humor and workplace stress: a longitudinal comparison between Australian and Chinese employees. (28th July 2017) - Wang, Rong; Chan, Darius Kwan Shing; Goh, Yong Wah; Penfold, Melissa; Harper, Timothy; Weltewitz, Tim
Abstract : This study investigates how humor usage (including positive and negative humor styles) influences employees' responses to the same stressful events, namely, the auto‐correlation between stress experiences at two time points. Moreover, it examines differences between Australian and Chinese employees in such effects via bicultural comparisons. Results from a two‐wave survey of 109 Australian and 141 Chinese employees indicated that humor usage moderated the StressTime1  – StressTime2 relationship for Australian employees but not for Chinese employees. Specifically, the positive relationship between the two stress measures became weaker for Australians who were higher in humor than those lower in humor. Similarly, Positive humor mitigated the relationship between StressTime1 and StressTime2 only for the Australians but not the Chinese. However, Negative humor exerted no influence on the focal relationship in either sample. Organizations should encourage employees to use humor in effective ways, thereby improving stress coping skills and reducing workplace stress. Key points: Chinese employees have lower levels of humor than Australian employees. Positive humor usage helps Australian employees reduce workplace stress. Both positive and negative humor styles are ineffective in reducing stress among Chinese employees.